Property Tax Research on Tax Rate Systems and Policies: Scopus and Sinta Indexed Journals - Sifaiyya, Yustisia; Andriani, Sri (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2025)
This study aims to determine the development of research related to property tax on the tax rate system and policy from 2000 to 2024. The method in this study is mixed methods, where quantitative research uses VOSviewer can describe how authors, keywords, and publications relate to each other. Thus, it helps researchers understand the research landscape and determine research paths that can have a significant impact. And qualitative with systematic literature review which is approach collects data and references from previous journals or articles. The findings in this study indicate an increase in the trend and number of publications on the topic of property tax. This study identifies a high preference for certain topics related to property tax in particular (tax system, tax rates, tax revenues, and local government) which is accompanied by the problem of property tax revenues that support local government into pros and cons and has the potential for further research.  However, this study has opened up opportunities for other researchers to further explore the development of research related to property tax and the government in considering the use of digitalization as a tax collection system.